Specification for nickel-chromium-titanium-aluminium heat-resisting alloy bar and wire for the manufacture of fasteners (maximum diameter or minor sectional dimension 25 mm) (nickel base, Cr 19.5, Ti 2.2, Al 1.4). (30th May 1975) - British Standards Institution
No abstract available